2018
DOI: 10.5334/jbsr.1515
|View full text |Cite
|
Sign up to set email alerts
|

Spectral CT Detection of Entrapped Gallstone Based on Z-effective Map

Abstract: of gallbladder stone (GBS) is based on ultrasound (US), due to its high accuracy (98%) [1]. When cholecystitis is clinically suspected, US is also the preferred first diagnostic method, to identify signs of inflammation and the causative stone [2]. In inconclusive cases, computed tomography (CT) can be required to confirm or exclude cholecystitis, with a lower accuracy for stone detection, ranging from 25-88 % [3]. The most recent spectral CT systems (dual-energy or spectral systems) are based on the principle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The utility of dual-energy CT in gallstone evaluation is currently uncertain and the available dual energy analysis tools are therefore not being routinely utilised by the reading radiologists at our hospital. Emerging studies have suggested that dual-energy CT technology, with the help of postprocessing analysis tools, may have the potential to increase the conspicuity of radiolucent gallstones, thereby improving visual detection [5]. Many studies have described the use of low (40 keV) and high (140 keV) keV monoenergetic reconstructions in visualising radiolucent gallstones with varying success [6-8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of dual-energy CT in gallstone evaluation is currently uncertain and the available dual energy analysis tools are therefore not being routinely utilised by the reading radiologists at our hospital. Emerging studies have suggested that dual-energy CT technology, with the help of postprocessing analysis tools, may have the potential to increase the conspicuity of radiolucent gallstones, thereby improving visual detection [5]. Many studies have described the use of low (40 keV) and high (140 keV) keV monoenergetic reconstructions in visualising radiolucent gallstones with varying success [6-8].…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol gallstones have a lower atomic number than bile. This difference in atomic number can be exploited to enhance their visibility on dual energy CT through applying colour LUT (Lookup Table ) overlays, selectively displaying all the atomic numbers within the available step gradients offered on the post processing software [5,7]. If DECT could effectively diagnose cholelithiasis and choledocholithiasis, this would reduce the need for further imaging using ultrasound and MRCP, permit earlier de nitive clinical decision making, decrease the length of hospital stay and reduce resource consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that computed tomography can help in detecting GB stones, especially with difficult and inconclusive cases or GB perforation, and is still recommended for abdominal pain evaluation, only if the diagnosis is uncertain (Harraz & Abouissa, 2020;Danse et al, 2018;Wertz et al, 2018). On the contrary, a CT scan is less accurate than ultrasound (US) imaging in detecting biliary stones and debatably the most effective for diagnosing gallbladder condition, especially for gallstone ileus and pancreaticobiliary tract evaluation (Veronica et al, 2019;Alshargi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%